2022
DOI: 10.7759/cureus.29176
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Disease and Its Association in Children With Down Syndrome

Abstract: The objective is to determine the frequency of different congenital heart diseases and their association in children with Down syndrome (DS). MethodologyThis cross-sectional observational study was conducted in the pediatric department of Peshawar Institute of Cardiology, Peshawar, Pakistan from August 2021 to July 2022. A total of 123 children with DS and congenital heart disease (CHD) were included in this cross-sectional study. Detailed history and examination were performed, and findings were documented on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…24 Rehman Y et al in 2022 at pediatric department of Peshawar Institute of Cardiology, supported the same finding as Mughal. 25 Aziz et al only inducted 18 Down syndrome cases which limit the generalization of results. 26 When gender was considered as a risk factor for causation of cardiac defect, the odds ratio was 1.72, suggesting that females may be more likely to experience a cardiac defect as compared to males but this association is not significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Rehman Y et al in 2022 at pediatric department of Peshawar Institute of Cardiology, supported the same finding as Mughal. 25 Aziz et al only inducted 18 Down syndrome cases which limit the generalization of results. 26 When gender was considered as a risk factor for causation of cardiac defect, the odds ratio was 1.72, suggesting that females may be more likely to experience a cardiac defect as compared to males but this association is not significant.…”
Section: Resultsmentioning
confidence: 99%
“… 24 Rehman Y et al in 2022 at pediatric department of Peshawar Institute of Cardiology, supported the same finding as Mughal. 25 Aziz et al only inducted 18 Down syndrome cases which limit the generalization of results. 26 …”
Section: Discussionmentioning
confidence: 99%
“…A recently conducted study by Rehman Y et al showed that 57% children with DS having CHDs had growth failure. We were unable to document the growth parameters in the present study but it is very important to identify and treat children with DS having CHDs so that growth indicators of the affected children can be improved 21.…”
mentioning
confidence: 87%
“…Por su parte, Rehman et al 46 , en el estudio transversal observacional realizado en el departamento de pediatría del Instituto de Cardiología de Peshawar, Pakistán, que incluyó 123 pacientes, 101 (82.1%) con cardiopatía congénita acianótica y 22 (17.8%) con cardiopatía congénita cianótica, el diagnóstico fue confirmado mediante ecocardiografía bidimensional (2D) y Doppler realizado por un cardiólogo pediatra.…”
Section: Nivel De Evidencia Bunclassified